Diketopyrrolopyrrole or benzodithiophene-arylamine small-molecule hole transporting materials for stable perovskite solar cells. Issue 90 (13th September 2016) - Liu, Xuepeng; Kong, Fantai; Tan, Zhan'ao; Cheng, Tai; Chen, Wangchao; Yu, Ting; Guo, Fuling; Chen, Jian; Yao, Jianxi; Dai, Songyuan
Abstract : Two new hole transporting materials with diketopyrrolopyrrole or benzodithiophene moieties were developed for stable perovskite solar cells. Abstract : Two simple small-molecular arylamine derivatives 4-methoxy- N -(4-methoxyphenyl)- N -(4-(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)phenyl)aniline (OMeTPA-DPP ) and 4, 4′-(4, 8-bis((2-ethylhexyl)oxy)benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl)bis( N, N -bis(4-methoxyphenyl)aniline) (OMeTPA-BDT ) linked with diketopyrrolopyrrole or benzodithiophene moieties have been synthesized. The new compounds show better thermal stability than spiro-OMeTAD. The steady-state and time-resolved photoluminescence demonstrate that the new compounds have good hole extraction ability. The perovskite solar cells employingOMeTPA-BDT show a comparable power conversion efficiency with that of spiro-OMeTAD. After more than 200 hours of aging under one sun illumination, the residual efficiencies of the PSCs based onOMeTPA-DPP, OMeTPA-BDT and spiro-OMeTAD are 8.69%, 11.15% and 9.08%, respectively. The results demonstrate that the newly-developed compounds can act as efficient hole transporting materials for stable perovskite solar cells.